2022
DOI: 10.1021/acsami.2c05794
|View full text |Cite
|
Sign up to set email alerts
|

Mineralized Enzyme-Based Biomaterials with Superior Bioactivities for Bone Regeneration

Abstract: The formation and metabolic balance of bone tissue is a controllable process of biomineralization, which is regulated by various cells, biomolecules, and ions. Enzyme molecules play an important role in this process, and alkaline phosphatase (ALP) is one of the most critical factors. In this study, inspired by the process of bone biomineralization, a biomimetic strategy is achieved for the preparation of mineralized ALP nanoparticles (MALPNs), by taking advantages of the unique reaction between ALP and calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…[16] Alkaline phosphatase (ALP), a common enzyme involved in in vivo biomineralization, can cleave phosphate esters and increase the local concentration of inorganic phosphate ions (Pi) that are necessary for hard tissue biomineralization. [17,18] ALP has been used to develop hybrid scaffolds of calcium phosphate (CaP) and polymers for bone tissue regeneration. [19][20][21] Using this approach, the mineralization rate of polymer scaffolds can be effectively controlled, resulting in denser and more uniform CaP deposits on the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Alkaline phosphatase (ALP), a common enzyme involved in in vivo biomineralization, can cleave phosphate esters and increase the local concentration of inorganic phosphate ions (Pi) that are necessary for hard tissue biomineralization. [17,18] ALP has been used to develop hybrid scaffolds of calcium phosphate (CaP) and polymers for bone tissue regeneration. [19][20][21] Using this approach, the mineralization rate of polymer scaffolds can be effectively controlled, resulting in denser and more uniform CaP deposits on the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers suggested that osteointegration depends not only on the chemical composition of the implant surface but also on the microstructure of the surface . Various types of surface modifications such as material coating, surface protein grafting, and increasing surface roughness have been applied to improve the osteointegration of the implant surface and the surrounding bone. , The excellent performance of natural bone is due to its multicomponent and hierarchical hybrid structure . From a bionic point of view, a hierarchical surface topography of the implant would be more favorable for osteogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…11,12 The excellent performance of natural bone is due to its multicomponent and hierarchical hybrid structure. 13 From a bionic point of view, a hierarchical surface topography of the implant would be more favorable for osteogenesis. 14 In our previous work, we have introduced a hydrothermal technique to fabricate Ti implants with phosphoric acid etching and a biomimetic hierarchical structure, which achieved upgraded performance in cell adhesion and early osteointegration.…”
Section: Introductionmentioning
confidence: 99%
“…Biomimetic scaffolds, primarily based on biopolymers, such as collagen, hyaluronic acid, and alginates, not only provide a minimal adverse immune response and are available in virtually unlimited quantities, but may also possess desirable osteoinductive and osteoconductive properties for more efficient bone reconstruction [6,7]. The combination of osteoinductive growth factors and osteoconductive hydrogel scaffolds tends to meet the requirements for synthetic bone substitutes in full, providing protein bioactivity in the implantation zone, as well as a microenvironment for newly formed tissue [8,9]. Bone morphogenetic proteins (BMPs) are considered to be crucial biomolecules for stimulating and promoting osteogenic differentiation in cells [10,11].…”
Section: Introductionmentioning
confidence: 99%